Feasibility analysis of the “Dentum Anak” application for early childhood education teachers : Dentum Anak - Ratna Indah Kartika Sari; Elsa Noftalina; Aspia Lamana; Arlina Rachmaida (Universitas Aisyiyah Yogyakarta, 2026)
Early childhood is a critical period requiring appropriate stimulation and developmental monitoring to ensure optimal growth and development. In Indonesia, approximately 14.3% of children experience developmental delays, highlighting the importance of early detection efforts. PAUD teachers play an important role in monitoring child development, however, limitations in knowledge and monitoring tools remain a challenge. Digital technology, particularly Android-based applications, offers an opportunity to support developmental screening practices. This study aimed to analyze the feasibility of the Dentum Anak application as a digital medium for early childhood growth and development monitoring. This study used a Research and Development (R&D) approach with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Twelve PAUD teachers were selected through purposive sampling. Data collection involved expert validation sheets and user feasibility questionnaires. The study was conducted over five months, from June to October 2025. Results showed media expert validation of 88.9%, material expert validation of 97%, and implementation testing with PAUD teachers of 88.9%, all categorized as very feasible. The Dentum Anak application is feasible for early detection of chid growth and development status.